2018
DOI: 10.1039/c8ra01807c
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid monitoring of doxorubicin using streptavidin-modified microparticle-based time-resolved fluorescence immunoassay

Abstract: Simple, rapid SA-MPs based TRFIA, is applied in therapeutic drug monitoring and the analytical performance is comparable with LC-MS/MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…According to literature, DOX has a stable UV absorption wavelength (around 480 nm) and red fluorescence emission of about 590 nm [ 30 ]. Therefore, the ability of DOX-Fe 3 O 4 @agar NPs to release the DOX drug was monitored by UV-vis spectrophotometer.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature, DOX has a stable UV absorption wavelength (around 480 nm) and red fluorescence emission of about 590 nm [ 30 ]. Therefore, the ability of DOX-Fe 3 O 4 @agar NPs to release the DOX drug was monitored by UV-vis spectrophotometer.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra (Figure 6) showed that Dox emitted a maximum fluorescence signal at approximately 590 nm, which agreed with results in the literature. 57 In addition, its fluorescence was quenched completely upon mixing with CAH, indicating complete intercalation at Dox to CAH molar ratio of 1:5. Dox has two major moieties in its structure: an amino sugar group and a tetracyclic core.…”
Section: Characterization Of Dox-cahmentioning
confidence: 99%
“…Using the scanning spectrophotometer we obtained a wavelength of fluorescence emission spectrum at ~580 nm, which is also consistent with previous researches (Chapman et al, 2016) (Fig 5a). We further conducted a linear regression analysis to evaluate the validity and the linearity of the concentration- Doxorubicin excitation wavelength was found at ~483 nm for concentrations range 1 -0.1 µM, which is consistent with previous studies (Liang et al, 2018) (Fig 7a). At the same concentrations, fluorescence emission wavelength was found ~592 nm (Fig 7b).…”
Section: Spectrophotometersupporting
confidence: 87%